Influence of bioremediation on the chemical and nutritional composition of produce from crude oil-polluted sites. - Odukoya, Johnson Oluwaseun (Cranfield University, 2015)
The influence of crude oil-contaminated and remediated sites on agrifood production is not clearly understood. To address this knowledge gap, the research was divided into two stages involving: (1) assessment of the efficiency of two bioremediation strategies to support hydrocarbons degradation as well as agrifood production with the initial analysis of the experimental materials, and (2) evaluation of the effect of different crude oil remediation intervention values (CRIV) on selected vegetables (Brassica juncea, Brassica oleracea, Lactuca sativa and two different cultivars of Solanum lycopersicum). Results from the first stage showed that the crude oil used had a pristane/phytane ratio of 0.98 (within the 0.8 – 3.0 range of most crude oils), higher concentrations of C₁₀ – C₁₄, C₁₅ – C₂₀ and C₂₁ – C₂₇ alkanes than the C₂₈ – C₃₆ alkanes including higher concentrations of two of the US EPA priority pollutant polycyclic aromatic hydrocarbons (PAHs) - phenanthrene and anthracene. Four treatments were prepared in which weekly tillage enhanced the degradation of C₁₅ – C₂₀ and C₂₁ - C₂₇ alkanes in the Remediation by Enhanced Natural Attenuation (RENA) treatment. The two bioremediation strategies (RENA and bioaugmentation) enhanced PAHs degradation compared with the remediation-study control treatment while only RENA application among the two approaches supported the growth of B. juncea. Although there was no statistical significant difference (p > 0.05) between the major dietary mineral contents of samples from the various treatments compared with the control treatment samples, RENA application affected the Cr, Zn and Pb contents. Meanwhile, the Ca/P (> 1.0) and Na/K (< 0.60) ratios of all the harvested samples imply that they provide a good source of these minerals for bone formation and would not contribute to high blood pressure. The crude oil used also deterred the attack of juvenile caterpillars of cabbage white butterfly. Findings from the second stage revealed that the yield of the green leafy vegetables including one of the selected tomato cultivars (Micro-Tom), was in most cases impaired at CRIV ≥ 3,000 mg/kg total petroleum hydrocarbon (TPH). Compared with the control treatment samples’ composition, crude oil stress at 10,000 mg/kg TPH enhanced the concentration ODUKOYA, Johnson O. Cranfield University PhD Thesis of K, Mn and crude protein of B. oleracea and L. sativa as well as the sucrose, total sugars, total phenolics and total flavonoids contents of the latter vegetable. Sucrose was also only detected in M82 tomato cultivar samples from the crude oil-containing treatments. The Cd content of B. oleracea, Pb contents of: L. sativa and M82 tomato harvested samples were all below the FAO/WHO Codex Alimentarius Commission 2015 recommended maximum levels. However, tartaric acid was only detected in B. oleracea and L. sativa samples from the 10,000 mg/kg TPH treatment as well as in M82 tomato cultivar samples from the treatment involving CRIV of 5,000 mg/kg TPH. Generally, the yield of these crops in response to crude oil contamination varied in which B. juncea had the least tolerance to crude oil stress among the green leafy vegetables tested. Most of the quality parameters in the two tomato cultivars were not affected by CRIV between 750 - 5,000 mg/kg TPH with p-xylene having the greatest toxic potential among the VOCs emitted from the 5,000 mg/kg TPH treatment. The research findings, under the experimental conditions, indicated the effectiveness of RENA for the degradation of low molecular weight PAHs and its agricultural benefits. They also suggest that crude oil-contaminated sites at ≤ 3,000 mg/kg TPH present a similar growing environment to a clean site for agrifood production and the possibility that crude oil stress at 10,000 mg/kg TPH could enhance crop quality. Nonetheless, the contribution of bio- accumulated PAHs in these crops to the food chain demands further investigation.
Keywords: Agrifood; Crude oil Remediation Intervention Values (CRIV); Remediation by Enhanced Natural Attenuation (RENA); Crop quality; Volatile Organic Compounds (VOCs); Vegetables